ʺImplementation of interactive learning methods in institutions of higher military education during the teaching of the discipline "Military Social Work" - Kuruch , A.; Mirshuk , O. (Problems of Engineer-Pedagogical Education, 2023)
The article examines the reformation of military education, in particular the humanitarian component. The necessity of implementing interactive training in institutions of higher military education has been proven, taking into account their specificity, since such training methods are very effective, as they allow to increase interest in the educational process and improve the assimilation of the material. The need to expand the cycle of humanitarian disciplines in institutions of higher military education, in accordance with the new functions of military specialists, in particular, such as civil-military cooperation, is considered. Examples of interactive classes that are used today in teaching the discipline "Military-Social Work" are considered, including role-playing games, group discussions, practical classes, problem-based lectures, and round tables. The current state of military social work in Ukraine and the need to expand the functions of social work in the military are analyzed. The functions of military social work in Ukraine are considered, including providing servicemen and their families with social support, which involves the organization of social and household services and ensuring interaction with the public, thus stimulating the development of military-civilian cooperation. It is the study of the discipline "Military social work" that helps to ensure the effectiveness of interaction with the public, to ensure high-quality information about the possibilities of social work in military teams, and also to maintain mutual understanding between the military and the public sector. It was concluded that in order to achieve the maximum result of training, it is necessary to combine the use of traditional and innovative forms of training. The topics of practical classes implemented in the discipline "Military and social work" at the National Academy of the National Guard of Ukraine were considered. It was concluded that today an important component of military-professional activity is cooperation with the civil sector, in particular with civil society institutions, religious organizations. Thus, using only traditional training methods, it is not possible to acquire skills that will help military personnel in civil-military cooperation. That is why interactive teaching methods are becoming increasingly useful today in higher military education institutions.